Fundidesulfovibrio magnetotacticus sp. nov., a sulphate-reducing magnetotactic bacterium, isolated from sediments and freshwater of a pond. Issue 9 (27th September 2022) - Shimoshige, Hirokazu; Kobayashi, Hideki; Shimamura, Shigeru; Miyazaki, Masayuki; Maekawa, Toru
Abstract : A sulphate-reducing magnetotactic bacterium, designated strain FSS-1 T, was isolated from sediments and freshwater of Suwa Pond located in Hidaka, Saitama, Japan. Strain FSS-1 T was a motile, Gram-negative and curved rod-shaped bacterium that synthesizes bullet-shaped magnetite (Fe3 O4 ) nanoparticles in each cell. Strain FSS-1 T was able to grow in the range of pH 6.5–8.0 (optimum, pH 7.0), 22–34 °C (optimum, 28 °C) and with 0–8.0 g l −1 NaCl (optimum, 0–2.0 g l −1 NaCl). Strain FSS-1 T grew well in the presence of 50 µM ferric quinate as an iron source. The major fatty acids were anteiso-C15 : 0, iso-C15 : 0 and anteiso-C17 : 0 . The major menaquinone was MK-7 (H2 ). Strain FSS-1 T contained desulfoviridin, cytochrome c 3 and catalase, but did not contain oxidase. Strain FSS-1 T used fumarate, lactate, pyruvate, malate, formate/acetate, succinate, tartrate, ethanol, 1-propanol, peptone, soytone and yeast extract as electron donors, while the strain used sulphate, thiosulphate and fumarate as electron acceptors. Fumarate was fermented in the absence of electron acceptors. Analysis of the 16S rRNA gene sequence showed that strain FSS-1 T is a member of the genus Fundidesulfovibrio . The gene sequence showed 96.7, 95.0, 92.0, 91.2 and 91.4% similarities to the most closely related members of the genera Fundidesulfovibrio putealis B7-43 T, Fundidesulfovibrio butyratiphilus BSY T, Desulfolutivibrio sulfoxidireducens DSM 107105 T, Desulfolutivibrio sulfodismutans ThAc01 T and Solidesulfovibrio magneticus RS-1 T, respectively. The DNA G+C content of strain FSS-1 T was 67.5 mol%. The average nucleotide identity value between strain FSS-1 T and F. putealis B7-43 T was 80.7 %. Therefore, strain FSS-1 T represents a novel species within the genus Fundidesulfovibrio, for which the name Fundidesulfovibrio magnetotacticus sp. nov. is proposed (=JCM 32405 T =DSM 110007 T ).